14 - EPIDEMIOLOGIC STUDY: INCIDENCE AND COMPLICATIONS OF TRANSFEMORAL AMPUTATION OF VASCULAR CAUSE (Fiep Bulletin - online, 2011)
Amputation is a word derived from Latin, which means the complete or partial removal of a body limb from different sources such as vascular, neuropathic, traumatic, tumoral, infectious and congenital. In Brazil, the incidence of amputations is estimated to be 13.9 per 100,000 inhabitants/year and in the USA the number is 4.9 per 1000 born alive babies, while this number is four times as high when we talk about people over 65 years old. As shown in books, the vascular disorders are the main cause of amputations and several pathologies and risk factors are associated with them such as tabagism and others. This article aimed to identify the incidence, as well as the main complications related to the transfemoral amputation of vascular cause. An epidemiologic study was accomplished at FAG's integrated clinics, interviewing 31 patients after they had signed a free agreement term document, the questionnaire application was accomplished. This questionnaire was composed by 31 questions, 8 subjective ones and 23 objective ones, and it was applied during one month, and from those patients 17 were selected according to the established criteria. In the research, 54.8% of the interviewees were from vascular cause, most of them (76.5%) were middle aged men, around 64 years old and the prevailing alteration in the stump was the phantom pain (70.6%). As it was previously thought, our average numbers were similar to what can be observed in the literature.
Keywords: Amputation; Transfemoral; Vascular cause